Effect of soil consolidation on the fractality of the filtration law - Panahov, Geylani; Museibli, Parviz; Sultanov, Babek (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the effect of consolidation of the soil structure on the fractality of the fluid flow was evaluated. The equation of fractal law of flow in the porous medium under consolidation of two-phase, fully fluid-saturated soil was determined. Given all the simplifications, as well as the undoubted importance of the nature of the porous medium, which primarily determine the possible processes of both consolidation and fractal flow based on the results of the studies, we can conclude that a homogeneous porous reservoir at given parameters under the effect of groundwater pressure will expand its fractal structure.
Keywords: soil; consolidation; fractals; filtration law; flow; porosity; rheology